PENGARUH BRAND IMAGE TERHADAP PENGAMBILAN KEPUTUSAN KONSUMEN DALAM MEMBELI PRODUK ORGANIK PADA BALI BUDA SHOP - Ni Ketut Desi Aristarini; Ni Nyoman Menuh (Forum Manajemen STIMI Handayani Denpasar, 2017)
The objective of this research is to understand the influence of Brand Image (the excellence of brand association, the strength of brand association, and the uniqueness of brand association) simultaneously and partially to customer’s decision to buy organic product in Bali Buda Shop. Sample is taken by using accidental sampling method with number of sample 100 respondents which are all customers in Bali Buda Shop. All data is collected by interview and questioner. Instrument is examined using validity and reliability test, classic assumption test. Data analysis technique uses multiple linier regression analysis, t test, f test, and determination analysis. The result of this analysis is that the excellence of brand associations, the strength of brand association, and the uniqueness of brand association give positive and significant impact simultaneously and partially to customer’s decision to buy organic product of Bali Buda. As for the suggestion given to the company is to distinguish the taste of the product to local and international customer’s to expand product distribution and to increase advertising.